Assessing the Role of AtGRP7 Arginine 141, a Target of Dimethylation by PRMT5, in Flowering Time Control and Stress Response - Steffen, Alexander (2024)
PROTEIN ARGININE METHYLTRANSFERASES (PRMTs) catalyze arginine (R) methylation that is critical for transcriptional and post-transcriptional gene regulation. In Arabidopsis, PRMT5 that catalyzes symmetric R dimethylation is best characterized. PRMT5 mutants are late-flowering and show altered responses to environmental stress. Among PRMT5 targets are Arabidopsis thaliana GLYCINE RICH RNA BINDING PROTEIN 7 (AtGRP7) and AtGRP8 that promote the transition to flowering. AtGRP7 R141 has been shown to be modified by PRMT5. Here, we tested whether this symmetric dimethylation of R141 is important for AtGRP7’s physiological role in flowering time control. We constructed AtGRP7 mutant variants with non-methylable R141 (R141A, R141K). Genomic clones containing these variants complemented the late-flowering phenotype of the grp7-1 mutant to the same extent as wild-type AtGRP7. Furthermore, overexpression of AtGRP7 R141A or R141K promoted flowering similar to overexpression of the wild-type protein. Thus, flowering time does not depend on R141 and its modification. However, germination experiments showed that R141 contributes to the activity of AtGRP7 in response to abiotic stress reactions mediated by abscisic acid during early development. Immunoprecipitation of AtGRP7-GFP in the prmt5 background revealed that antibodies against dimethylated arginine still recognized AtGRP7, suggesting that additional methyltransferases may be responsible for modification of AtGRP7.